[OP.3B.05] HEXARELIN PRESERVES MYOCARDIAL FUNCTION AND REDUCES INFLAMMATION AND FIBROSIS IN A MOUSE MODEL OF MYOCARDIAL ISCHEMIA REPERFUSION. (September 2017) - Mcdonald, H.; Peart, J.; Kurniawan, N.D.; Galloway, G.; Royce, S.G.; Samuel, C.S.; Chen, C.
Abstract : Objective: Growth hormone secretagogues (GHS) have been demonstrated to improve cardiac function, attenuate inflammation and modulate the autonomic nervous system in models of ischemic heart disease (IHD). This study aimed to determine whether hexarelin (HEX), a synthetic GHS, preserves cardiac function and attenuates inflammation and remodelling using a mouse model of myocardial ischemia reperfusion (IR). Design and method: Myocardial ischemia was induced by transient ligation of the left descending coronary artery (LAD) in C57BL/6J mice followed by HEX (n = 18) or vehicle (VEH) (n = 17) administration at 0.3 mg/kg/day for 21 days. Treated and sham mice were subjected to magnetic resonance imaging using a T1-weighted late gadolinium enhancement sequence (LGE) at 9.4 Tesla (T) to measure left ventricular (LV) function and tissue characteristics after 24 hours and 21 days. Results: HEX mice demonstrated a significant improvement in cardiac function compared with the VEH-treated group, demonstrating preservation of both systolic and diastolic function. A significant decrease in interstitial collagen and collagen concentration was demonstrated after 21 days within the HEX group. This was accompanied by a decrease in TGF-beta1 and alpha-SMA. Heart rate variability (HRV) analysis demonstrated that HEX treatment shifted the balance of autonomic nervous activity towards a parasympathetic predominance, evidenced by a smaller low/high-frequency power ratio (LF/HF) and increased normalized high frequency power (nHF). This was combined with a significant decrease in Troponin-I (CnT-I) and TNF-alpha levels with HEX treatment. Conclusions: These results demonstrate that GHS may preserve ventricular function and prevent remodelling in models of myocardial IR. The protective effects of HEX might be attributed to rebalancing the deregulated autonomic nervous system and activation of the cholinergic anti-inflammatory pathway (CAP) in myocardial IR.